A Child With a Burn-Related Foot and Ankle Contracture Treated With Multiple Modalities. Issue 1 (January 2017) - Yelvington, Miranda; Scoggins, Michelle; White, Leslie
Abstract : Purpose: The presence of hypertrophic scars, which cross lower extremity joints, can often result in decreased range of motion, limitations in functional mobility, and gait deviations. This article reviews a case and describes a multimodal treatment approach. Summary of Key Points: A 6-year-old girl developed aggressive hypertrophic scars following a burn injury. A multimodal treatment approach, including splinting, elastomers, and physical therapy, was developed. Conclusions: Rapid improvements were demonstrated in measured objective outcomes. Recommendations for Clinical Practice: Early multimodal intervention, in addition to range of motion, stretching, massage, and compression garments, is recommended when treating hypertrophic scars. This case suggests that further study into a multimodal treatment approach may be beneficial to develop a standardized protocol for more efficient scar management. Abstract : Supplemental Digital Content is Available in the Text.A case report featuring a multi-modal intervention to address functional mobility limitations and gait deviations related to hypertrophic scars in a child burn survivor.